A global call from five countries to collaborate in antibiotic stewardship: united we succeed, divided we might fail. Issue 2 (February 2017) - Goff, Debra A; Kullar, Ravina; Goldstein, Ellie J C; Gilchrist, Mark; Nathwani, Dilip; Cheng, Allen C; Cairns, Kelly A; Escandón-Vargas, Kevin; Villegas, Maria Virginia; Brink, Adrian; van den Bergh, Dena; Mendelson, Marc
Summary: In February, 2016, WHO released a report for the development of national action plans to address the threat of antibiotic resistance, the catastrophic consequences of inaction, and the need for antibiotic stewardship. Antibiotic stewardship combined with infection prevention comprises a collaborative, multidisciplinary approach to optimise use of antibiotics. Efforts to mitigate overuse will be unsustainable without learning and coordinating activities globally. In this Personal View, we provide examples of international collaborations to address optimal prescribing, focusing on five countries that have developed different approaches to antibiotic stewardship—the USA, South Africa, Colombia, Australia, and the UK. Although each country's approach differed, when nurtured, individual efforts can positively affect local and national antimicrobial stewardship programmes. Government advocacy, national guidelines, collaborative research, online training programmes, mentoring programmes, and social media in stewardship all played a role. Personal relationships and willingness to learn from each other's successes and failures continues to foster collaboration. We recommend that antibiotic stewardship models need to evolve from infection specialist-based teams to develop and use cadres of health-care professionals, including pharmacists, nurses, and community health workers, to meet the needs of the global population. We also recommend that all health-care providers who prescribe antibiotics take ownership and understand the societal burden of suboptimal antibiotic use, providing examples of how countries can learn, act globally, and share best antibiotic stewardship practices.